PRESSURE- AND LODE-DEPENDENT YIELD CRITERION WITHIN THE PROBLEM OF 2024-T3(51) ALUMINUM ALLOY PLATE PERFORATION BY A RIGID PROJECTILE - Vladislav V. Vershinin; Vladimir I. Mondrus (International Journal for Computational Civil and Structural Engineering, 2017)
The problem of perforation of free circular plates made of 2024-T3(51) aluminum alloy or its Russian analogue D16(A)T with various thicknesses normally impacted at their centers by a rigid spherical projectile is considered. The considered problem is numerically simulated through the finite element method utilizing phenomenological pressure- and Lode-dependent yield and fracture criteria along with an associated flow rule and a linear damage accumulation law to describe the target material deformation and fracture. Comparison of the obtained results with the experimental data as well as with the numerical results calculated using less sophisticated phenomenological material models is made. Necessity of a yield criterion pressure and Lode dependence to provide accuracy of numerical simulation is assessed.